Fatal Ovarian Hemorrhage Associated With Anticoagulation Therapy in a Yucatan Mini-Pig Following Venous Stent Implantation - Boorman, Sophie; Douglas, Hope; Driessen, Bernd; Gillespie, Matthew J.; Schaer, Thomas P. (Frontiers in Veterinary Science, 2020)
Swine models are commonly utilized in endovascular research for development of intravascular interventions and medical device development. As part of a pilot study for a venous vascular stent device, a 5-year-old female Yucatan mini-pig underwent bilateral external iliac vein stent placement under general anesthesia. To reduce thrombotic complications by reduction of thrombus formation on wires, sheaths, and catheters, the pig was heparinized with a total of 300 IU/kg of heparin, establishing an activated clotting time (ACT) of 436 seconds. The ACT had returned to below 200 seconds by the end of the procedure. To prevent postoperative thrombosis, the pig received an anticoagulation therapy protocol consisting of enoxaparin, clopidogrel and aspirin. There were no complications during the immediate postoperative period. However, the pig died 4 days after surgery. Necropsy established the cause of death as abdominal exsanguination due to severe, acute, intra-ovarian hemorrhage, most likely related to ovulation. Life-threatening ovarian hemorrhage is occasionally seen in women with congenital or acquired bleeding disorders; to our knowledge this is the first report of fatal ovarian hemorrhage in an animal enrolled in a pre-clinical research trial.